The Distribution of Wealth and the MPC: Implications of New European Data - Carroll, Christopher D.; Slacalek, Jiri; Tokuoka, Kiichi (American Economic Review, 2014)
Using a standard, realistically calibrated model of buffer-stock saving with transitory and permanent income shocks, we study how cross-country differences in the wealth distribution and household income dynamics affect the marginal propensity to consume out of transitory shocks (MPC). Across the 15 countries in our sample, we find that the aggregate consumption response ranges between 0.1 and 0.4 and is stronger (i) in economies with large wealth inequality, where a larger proportion of households has little wealth, (ii) under larger transitory income shocks, and (iii) when we consider households only use liquid assets (rather than net wealth) to smooth consumption.